Dope dyeing of lyocell fiber with NMMO-based carbon black dispersion. (15th October 2017) - Zhang, Liping; Sun, Weize; Xu, Dan; Li, Min; Agbo, Christiana; Fu, Shaohai
Highlights: NMMO-based CB dispersion is prepared and characterized. The properties of dispersion rely on structure and amount of dispersant. NMMO-based CB dispersion has excellent compatibility with lyocell spinning solution. The properties of dope dyeing fiber are affected by CB content. Abstract: NMMO-based carbon black (CB) dispersion was prepared and its properties as well as its compatibility with lyocell spinning solution were further investigated. Modified lignosulfonate (SP) was verified to be the preeminent dispersant for the preparation of NMMO-based CB dispersion with mass ratio of SP to CB 20% and water to NMMO 13%. The compatibility of NMMO-based CB dispersion with lyocell spinning solution had close relation with dispersant structure and CB content. Mass ratio of CB to cellulose affects the mechanical properties, color strength and crystallinity of lyocell fiber. 0.5% CB increased the breaking strength and elongation of lyocell fiber, whiles breaking strength and elongation of the lyocell fiber were reduced slightly when 2.0% CB was used. The dope dyed fiber showed excellent rubbing and washing fastness as well as migration resistance to water, ethanol and acetone.